Analisis Pengaruh Job Transfer Terhadap Kinerja Perawat Yang Dimediasi Motivasi Serta Peran Self Efficacy Sebagai Variabel Moderasi (Studi Pada Rumah Sakit Universitas Muhammadiyah Malang) - Titis Widayanti; Survival; Muchlis Mas’ud; Adya Hermawati; Nasharuddin Mas (Bajang Institute, 2026)
Abstrak: This study aims to examine and analyze the effect of job transfer on nurse performance at University of Muhammadiyah Malang Hospital, with motivation as a mediating variable and self efficacy as a moderating variable. The study is motivated by the importance of improving nurses' performance as a key factor in enhancing the quality of hospital services. Job transfer is considered one of the human resource management strategies expected to improve nurses' competencies, work experience, and performance. However, previous studies have reported inconsistent findings regarding its effectiveness, highlighting the need to investigate the roles of motivation and self efficacy in this relationship. The research method used is a quantitative approach with method totally sampling and population in this study consisted of 70 nurses who had experienced job transfers at the University of Muhammadiyah Malang Hospital. Data analysis techniques used Partial Least Square-Structural Equation Modeling (PLS-SEM) assisted by SmartPLS ver. 4.0 software to test the relationships between variables in a moderated mediation model. The variables included in this study are Job transfer, Nurses' Performance, Motivation, and Self-Efficacy. The results of this study provide empirical evidence regarding the following: (1) job transfer affects nurse performance; (2) job transfer affects motivation; (3) motivation affect nurse performance; (4) self efficacy affects nurse performance; (5) motivation mediate the effect of job transfer on performance improvement; and (6) self efficacy moderate the effect of motivation on nurse performance. These findings are expected to serve as a strategic foundation for hospital management in formulating transfer policies that are more planned and human-centric, with the aim of enhancing the quality of nursing services.